Kinetics and Mechanism of Bromination of Tris(Acetylacetates) of Co(III), Cr(III) and Bis(Acetylacetonato) Co(II) by Pyridinium Bromochromate in Aqueous Acetic Acid Medium - Raman , N.; Ramalingam, S.K. (Asian Journal of Chemistry, 2010)
The kinetics of bromination of Cr(acac)3, Co(acac)3 and Co(acac)2 by pyridinium bromochromate(PBC) in aqueous acetic acid have been studied under pseudo-first order conditions Co(III), Cr(III) acetylacetonates undergo electrophilic γ-substitution yielding M(Bracac)3 whereas Co(II) acetylacetonate undergoes nucleophilic bromination, yielding [CoBr4][PyH]2. The rate for the tris-chelates is dependent on the concentration of the reagent(PBC) and not the substrate. For the bis-chelate, the rate is dependent on both the substrate and the reagent. Probable mechanistic pathways for the bromination of the two cases are presented. A rate law is derived for the electrophilic γ-substitutions in metal(III) chelates.